The in vitro effects of a polyphenol epigallocatechin gallate on the cell viability, adhesion, and morphology of melanoma and endothelioma cells - Hlophe, Yvette Nkondo (University of Pretoria, 2024)
Dissertation (MSc(Human Physiology))--University of Pretoria, 2024.